National Culture and Human Resources Management of Transnational Companies - Boyratan, Asadul Usud; Herawati, Niken; Hidayat, Aris (STKIP Yapis Dompu, 2022)
The national culture of each country is certainly different. It certainly contains a cultural direction that influences the character of the citizens of that country. The character of each country's human resources is clearly shaped by the national culture adopted. In the business world, it is possible for a country to open a business unit in a country that they perceive as having an accommodative investment climate. No wonder an automotive manufacturer from Japan, for example, will set up its industry in Thailand, Vietnam, Latin America, to the European region. This study will look at the extent to which the role of national culture influences work culture in the company. Likewise, a country's company in transferring the management of Human Resources (HR) to its subsidiaries in various countries. This research is a qualitative literature review with descriptive method, corporate culture differs in one country and another where the company is located. Then the conclusion that can be drawn is that the management of manpower will depend on the national culture of the country.